2019
DOI: 10.4236/oalib.1105323
|View full text |Cite
|
Sign up to set email alerts
|

Boards of Directors’ Characteristics and Firm Value: A Comparative Study between Egypt and USA

Abstract: Purpose This research aims to compare the effect of board of directors' characteristics on the firm's value in Egypt as an emerging country and USA as a developed country. Five characteristics have been exposed from the literature review that may influence the enhancement of a firm's value. In corporate governance, these characteristics are CEO duality, board independence, board size, board meetings and gender diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 37 publications
8
27
0
3
Order By: Relevance
“…Therefore, the large amount of BOD can be highly effective in making decisions, so that it will affect the value of the company. This result is in accordance with the research of Yacob et al(2019), Salem et al(2019) and Kao, Hodgkinson, & Jaafar(2019) which state that the role of directors is very necessary in carrying out the interests and goals of the company, so that the large number of directors will provide a form of supervision for better company performance, good company performance is able to increase stock prices and firm value also increases.…”
Section: Analysis Researchsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, the large amount of BOD can be highly effective in making decisions, so that it will affect the value of the company. This result is in accordance with the research of Yacob et al(2019), Salem et al(2019) and Kao, Hodgkinson, & Jaafar(2019) which state that the role of directors is very necessary in carrying out the interests and goals of the company, so that the large number of directors will provide a form of supervision for better company performance, good company performance is able to increase stock prices and firm value also increases.…”
Section: Analysis Researchsupporting
confidence: 87%
“…Several research results indicate that the size of the board of directors can have a positive or negative impact on firm value. Salem et al(2019) found that in the USA and Egypt, board size has a positive effect on firm value. Ciftci et al(2019) also found a positive effect of the board of directors on firm value.…”
Section: Literature Review Board Of Director and Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Selain faktor Profitabilitas, stuktur modal dan ukuran perusahaan yang mempengaruhi nilai perusahaan adalah karakteristik dewan. Pernyataan ini disetujui oleh penelitian Salem et al (2019) yang mengungkapkan karakteristik dewan memiliki pengaruh positif terhadap nilai perusahaan. Menurut Kartikaningrum (2016) karakteristik dewan terdiri dari ukuran dewan, jumlah keberadaan independensi, jumlah keberagaman gender, serta frekuensi rapat dewan.…”
Section: Pendahuluanunclassified
“…Perusahaan Kompas 100 periode 2019-2020 merupakan populasi dalam penelitian ini. Kompas 100 dipilih karena memiliki likuiditas tinggi, nilai kapitalisasi pasar besar, fundamental dan kinerja optimal di BEI (Djumena, 2019) Dualitas CEO adalah situasi dimana CEO dan ketua dewan dipegang dengan orang yang sama dalam suatu perusahaan (Salem et al, 2019). Pengukuran Dualitas CEO dilakukan dengan cara variabel dummy = Peneliti akan menggunakan poin '1' untuk perusahaan yang memiliki dualitas CEO dan '0' untuk perusahaan yangtidak memiliki Dualitas CEO.…”
Section: Metode Penelitianunclassified